2018
DOI: 10.1021/acscatal.8b01751
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation on a Au/TiO2 Nanoparticle Catalyst via the Au-Assisted Mars–van Krevelen Mechanism

Abstract: Recently, there has been increasing evidence that CO oxidation on TiO2 supported Au catalysts proceeds predominantly via a Au-assisted Mars–van Krevelen mechanism for reaction temperatures of 80 °C and above. We here present results of a combined experimental and theoretical study, aiming at the identification of activated steps in this reaction. O2 multipulse experiments, performed in a temporal analysis of products (TAP) reactor at different temperatures between −80 and +240 °C, revealed that the replenishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 88 publications
11
124
0
1
Order By: Relevance
“…This is in agreement with our earlier work, where we showed that this is partly due to the polarisable nature of the Au 10 cluster which stabilises the change in oxidation state of surface Fe cations on the removal of an oxygen anion and partly due to charge transfer to the Au 10 cluster itself. A similar effect has also been found in calculations for Au supported on other oxide surfaces, for example Au/TiO 2 . For the grooved surface, several different types of surface O are present.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in agreement with our earlier work, where we showed that this is partly due to the polarisable nature of the Au 10 cluster which stabilises the change in oxidation state of surface Fe cations on the removal of an oxygen anion and partly due to charge transfer to the Au 10 cluster itself. A similar effect has also been found in calculations for Au supported on other oxide surfaces, for example Au/TiO 2 . For the grooved surface, several different types of surface O are present.…”
Section: Resultssupporting
confidence: 90%
“…A similar effect has also been found in calculations for Au supported on other oxide surfaces, for example Au/TiO 2 . [35] For the grooved surface, several different types of surface O are present. We have concentrated on two co-ordinate oxygen anions as these give rise to low defect creation energies.…”
Section: Dft Studies: the Role Of Support Surface Structure On The Avmentioning
confidence: 99%
“…Incorporation of aliovalent dopants into the lattice of host oxide often facilitated the formation of oxygen vacancies on the catalyst surface and induced oxygen species, which affected the CO oxidation of the oxide catalysts . Among the three typical reaction mechanisms describing catalytic CO oxidation such as Langmuir‐Hinshelwood (LH), Eley‐Rideal (ER), and Mars‐van Krevelen (MvK), the MvK mechanism in which the surface is an active reaction component has been particularly used to describe the consecutive processes of CO oxidation on metal oxide catalysts . As shown in Figure , this mechanism consists of two CO oxidation processes with different sources of the oxidizing oxygens.…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 99%
“…[42][43] Among the three typical reaction mechanisms describing catalytic CO oxidation such as Langmuir-Hinshelwood (LH), Eley-Rideal (ER), and Mars-van Krevelen (MvK), the MvK mechanism in which the surface is an active reaction component has been particularly used to describe the consecutive processes of CO oxidation on metal oxide catalysts. [19,[44][45][46][47] As shown in Figure 1, this mechanism consists of two CO oxidation processes with different sources of the oxidizing oxygens. The first one makes use of a lattice oxygen on the clean CeO 2 surface, while the second one uses the oxygen atom from an oxygen molecule which adsorbs onto the surface by recovering an oxygen vacancy.…”
Section: Reducibility Improvement On Catalyst Surfacementioning
confidence: 99%
“…Recently, PBE+U calculations performed on an Au nano‐rod supported on a TiO 2 anatase (101) substrate confirmed that the presence of the Au nano‐rod leads to a significant reduction of the vacancy formation energy at these sites, resulting in a barrier for CO oxidation following a MvK mechanism of only ∼0.9 eV. The reverse process, replenishing the vacancies by reaction with O 2 , was found to be activated in the case of individual vacancies, but essentially barrier‐free for the case of pairs of neighboured vacancies …”
Section: Applications In Heterogeneous Catalysismentioning
confidence: 99%